Notch Signaling Regulates Muscle Stem Cell Homeostasis and Regeneration in a Teleost Fish - Sultan, Sami H. A.; Dyer, Carlene; Knight, Robert D. (Frontiers in Cell and Developmental Biology, 2021)
Muscle regeneration is mediated by the activity of resident muscle satellite cells (muSCs) that express Pax7. In mouse Notch signalling regulates muSCs during quiescence and promotes muSC proliferation in regeneration. It is unclear if these roles of Notch in regulating muSC biology are conserved across vertebrates or are a mammalian specific feature. We have therefore investigated the role of Notch in regulating muSC homeostasis and regeneration in a teleost fish, the zebrafish. We have also tested some fundamental questions regarding how resident muSCs respond to injury: 1) is injury size correlated with the magnitude of the muSC response, 2) how comparable are muSC responses between different stages of larval development. We show that in an absence of injury Notch is important for maintaining muSC quiescence at the myoseptum. In contrast, Notch signalling promotes proliferation and prevents differentiation in the context of injury. Although we note a stronger muSC response to injury at later larval stages Notch is required for the proliferative response at early and late larval stages. These results reveal a conserved role for Notch signalling in maintaining muSC quiescence and for promoting proliferation during regeneration in teleost fish and mammals.